Teknik Budi Daya Dan Karakteristik Talas Belitung (Xanthosoma sagittifolium) di RW 01 Kelurahan Situ Gede - Reynatha Syafira Rizkiya; Fitrianingrum Kurniawati (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Taro is one of the most cultivated plant in Bogor. One of the area that routinely producing taro is Situ Gede. There are two types of taro that commonly cultivated, belitung’s taro (Xanthosoma sagittifolium) and bogor’s taro (Colocasia esculenta L.). In Situ Gede, they only cultivating belitung’s taro (Xanthosoma sagittifolium). Planting and cultivating taro is not hard but the uncorrect way to cultivate taro can cause the yield not at its maximum. It still need a proper way of cultivation to gain maximum yield. This writing aims to know the cultivation technique and the characteristic of belitung taro (Xanthosoma dagittifolium) which is cultivated by the community of RW 01, Situ Gede village. This activity held in RW 01 Situ Gede on 19 of February 2020 to 3 of March 2020. The data’s taken with interviewing and observing the real situation. The data will be compared to literature with the same topic. The process of taro cultivation in Situ Gede village starts from the preparation of planting material which is propagated by itself from tubers, making beds, organic and inorganic fertilizing with different intervals, weeding and land disposal process for the purpose of production. Taro saplings are not discarded but are used for taro propagation. In general, the cultivation techniques applied in Situ Gede are in accordance with the literature and some taro farming practices in other areas. The number of tubers produced is largely influenced by environmental factors, spacing, and intensity of care in the cultivation process. Keywords: belitung’s taro, characteristic, cultivation, tuber